Ethanolic extract of gabirobeira (Campomanesia adamantium) leaves reduces proliferation of osteosarcoma cells in vitro (Acta Scientiarum. Biological Sciences, 2021)
Osteosarcoma is the most commonly diagnosed malignant bone tumor in humans, with a higher incidence in children and young people. It is highly aggressive and has a high metastatic potential. Its treatment is based on both chemotherapy and surgical intervention. However, currently used chemotherapeutic agents, such as doxorubicin, have several adverse effects on the patient. Therefore, there is a growing demand for new chemotherapeutic agents that stimulate new researches, such as those involving compounds extracted from plants, such as the gabirobeira. In this study, we aimed to evaluate the cytotoxic effects of ethanolic extract, both crude and ethyl acetate, of gabirobeira leaves on osteosarcoma cells in vitro. Cytotoxicity was evaluated using the Trypan blue exclusion method and the IC50 values were calculated using the tetrazolium reduction method. The ethanolic extract of gabirobeira leaves showed a cytotoxic effect on osteosarcoma cells in vitro. The group treated with the crude extract at 1. 0Î¼L mL-1 concentration for 48 hours showed higher cytotoxicity and the lowest IC50 value for this extract was found in the 24 to 48 hours interval. The ethanolic extract of gabirobeira leaves is cytotoxic for osteosarcoma cells.